Future of sugarcane in South America: climate adaptation based on CMIP6 scenarios - Torsoni, Guilherme Botega; de Oliveira Aparecido, Lucas Eduardo; Lorençone, João Antonio; Lorençone, Pedro Antonio; de Souza Rolim, Glauco; de Souza Schlick, Genivaldo David (Acta geophysica, 2025)
This article tackles the challenge of adapting the climatic zoning of sugarcane in South America to the climate changes projected by the Coupled Model Intercomparison Project Phase 6 (CMIP6). Climate change poses a serious threat to the viability of sugarcane cultivation across the continent. Air temperature and daily rainfall data for the current climate scenario were obtained from the WorldClim version 2.1 platform (FICK; HIJMANS, 2017) in GeoTiff format, representing the latest climatological normal. Data for future climate scenarios were acquired from the WorldClim 2.1 platform using the IPSL-CM6A-LR model. These data cover four periods 2021–2040, 2041–2060, 2061–2080, and 2081–2100. Additionally, data for four Shared Socioeconomic Pathways (SSP) scenarios were utilized, namely: SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5, which are sequentially from the most optimistic to the most pessimistic. Sugarcane suitability zoning for South America was created using QGIS software, with the process automated using Python scripts. The climatic zoning for the current period presented nine climatic classes, with a predominance of the “Non-cultivated Areas” class (40.3%), followed by the “Unsuitable due to Thermal Excess and Water Deficiency” class (22.6%), and in fourth place the “Suitable” class (9.0%). The SSP5-8.5 scenario alters the climatic zoning for sugarcane in all periods. Suitability class decreases in all periods, with an average for the periods of 8.4% (2021–2040), 7.0% (2041–2060), 6.4% (2061–2080), 5.0% (2081–2100). The SSP2-4.5 scenario presents more plausible and likely results for future scenarios. It shows a potential increase of 8% in the “Unsuitable” class due to thermal excess and water deficit, with an average of 30.7%. Ultimately, our findings show that climate change may lead to a reduction in suitable areas for sugarcane cultivation, especially in the long term (2081–2100).